INTERNALISASI PERMAINAN TRADISIONAL PADA PELAJARAN SENI BUDAYA DAN PRAKARYA UNTUK MEMBANGUN KARAKTER ANAK SEKOLAH DASAR - Mariani, Ni Nyoman (Institut Hindu Dharma Negeri Denpasar, 2017)
As a formal educational institution, schools are responsible for the character education of children. Children are the generation that will become the successor of the nation. For that children need to be prepared as early as possible education that builds the character of children such as slipping a traditional game in subjects, especially subjects of Cultural Arts and Workshops. In the traditional game tucked many messages that should be conveyed by teachers to foster children's character, so that children have provisions to face real life in the community.Basically the world of children is a world of play. Playing is a very important and fun activity in children's learning process. Through child play will be encouraged to experiment and grow well in life. Traditional games have so many different forms and variations. Traditional games tend to utilize the tools or facilities in our environment without having to buy it so it needs a high imagination and creativity. The traditional dominant game involves a relatively large number of players, so it is not surprising to see almost all the popular games of so many of its members. Besides giving priority to the common pleasure factor, this game also has more intention to deepening interaction ability among players.Besides traditional games are also loaded with noble values and certain moral messages such as values of togetherness, honesty, responsibility, attitude field of chest (if lost), encouragement of achievement, and obedience to the rules. All that is obtained if the player really enjoy, enjoy, and understand the essence of the game.